DISTORSI SEJARAH DAN PERSEPSI VISUAL: STUDI KASUS ANIMASI POCAHONTAS - Virginia Suryani Setiadi; Anisha Melanie Yuniar S; Wegig Murwonugroho; Ekananda Haryadi (Universitas Mercu Buana, 2023)
As a form of children's literature, animated films are reflective illustrations of real life whose consumers are segmented as children. However, children's literary production is often ambivalent. The reason is that children's literature must arouse the imagination (in order to fulfill the elements of literature) while depicting real life that represents facts (in order to fulfill the requirements for reflection and representation of life). If animation is used to retell past history, then the major premise narrated by the animation must be representative of actual events (valid in terms of the information source). This research seeks to achieve two things, namely: discussing the extent of historical distortion in the Pocahontas animation as literature, and revealing the audience's meaning of the message content in the Pocahontas animation. This research was carried out qualitatively using the structuralism semiotic analysis method introduced by Ferdinand de Saussure. The results of this research reveal that the historical reconstruction in the Pocahontas animation is indeed distorted. However, this deviation is still at a normal stage as children's literature. The Pocahontas animation does not qualify as a historical reconstruction. It only qualifies as children's literature intended for entertainment purposes. Moreover, there is the addition of the wrong romantic element. According to a semiotic analysis of audience perception, this distortion is not a serious problem for viewers in Indonesia (who incidentally do not know the historical events behind the character Pocahontas). Meanwhile, for Americans, especially native Americans, this distortion is an ethical problem that literary producers and critics need to pay attention to.